A heroína na arquitetura transacional de Senhora - Almeida, Débora Cristina de (2018)
The present dissertation aims at verifying how Aurelia Camargo’s discourse, heroine of the novel Senhora (1875), written by José de Alencar, relates to the discourse the other characters, as well as the consequences of this relation to the process of ideological construction of the heroin and the representation of this process in the structure of the novel. By commencing with the presentation of Aurelia in the light of different theories on the construction of the fictional character, we move on to an overview of the feminine imaginary in the Brazilian 19th century novel and then to considerations about the female archetypes in Jose de Alencar’s novels. The present study, then, culminates with the analysis of the aforementioned novel. Based on Robert Schwarz’s sociological critics and Bakhtin’s ideas concerning the exotopy and the heterodiscourse in the novel, this analysis presents some considerations about the ideological transformation Aurelia Camargo goes through with the intent of relating it to the development of the plot since her process acts as a centripetal force over the novel’s narrative scheme